2018
DOI: 10.1039/c8md00149a
|View full text |Cite
|
Sign up to set email alerts
|

A synthetic diphosphoinositol phosphate analogue of inositol trisphosphate

Abstract: a Diphosphoinositol phosphates (PP-InsPs) are inositol phosphates (InsPs) that contain PP (diphosphate) groups. Converting a phosphate group in an InsP into a diphosphate has been reported to enhance affinity for some binding proteins. We synthesised 1-PP-InsIJ4,5)P 2 , the first diphosphate analogue of the intracellular signalling molecule InsP 3 , and examined its effects on InsP 3 receptors, which are intracellular Ca 2+ channels. 1-PP-InsIJ4,5)P 2 was indistinguishable from InsP 3 in its ability to bind to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Biochemical assays have indicated that the 5-β-phosphate is preferentially cleaved from 1,5-InsP 7 [ 14 ]. Despite that, these enzymes show a greater preference for the 1-β-phosphate of 1-InsP 7 compared to the 5-β-phosphate of 5-InsP 7 [ 14 , 35 ]. Moreover, PCP analogs have been useful in validating the enzyme’s preference for 1-InsP 7 over 5-InsP 7 .…”
Section: The Positional Specificity Of Dipps: Information Gained Fmentioning
confidence: 99%
See 4 more Smart Citations
“…Biochemical assays have indicated that the 5-β-phosphate is preferentially cleaved from 1,5-InsP 7 [ 14 ]. Despite that, these enzymes show a greater preference for the 1-β-phosphate of 1-InsP 7 compared to the 5-β-phosphate of 5-InsP 7 [ 14 , 35 ]. Moreover, PCP analogs have been useful in validating the enzyme’s preference for 1-InsP 7 over 5-InsP 7 .…”
Section: The Positional Specificity Of Dipps: Information Gained Fmentioning
confidence: 99%
“…Moreover, PCP analogs have been useful in validating the enzyme’s preference for 1-InsP 7 over 5-InsP 7 . PCP analogs are not hydrolyzed by DIPPs, but by competing with the active site, they act as inhibitors of PP-InsP hydrolysis [ 25 , 26 , 35 ]. Fiedler and colleagues showed that 1-PCP-InsP 7 is an 80-fold more potent inhibitor of DIPP activity than is 5-PCP-InsP 7 [ 26 ].…”
Section: The Positional Specificity Of Dipps: Information Gained Fmentioning
confidence: 99%
See 3 more Smart Citations